Leadership Excellence in East and West: Reports from the Trenches - G. J. Hofstede; R. M. Dooley (Department of Management, Faculty of Economics and Business, Brawijaya University, 2017)
This article shows that leadership excellence is not uniformly perceived in one multinational. This study was done in a company active mainly in the USA, Malaysia and Singapore, half the management population (414 managers) joined in 39 focus sessions to define leadership excellence. This provided 4000 statements. 105 themes were extracted and submitted to exploratory factor analysis. The seven factors that emerged signify leadership styles. They were labeled: dependable optimist, approachable helmsman, focused people developer (universal); caring parent, proactive guide (eastern); passionate professional, vision-implementing team player (western). The main finding in one company there is partial, but not full consensus about excellent leadership. The findings are practical and they have a message about deep cross-cultural differences. The themes are relevant for leadership development in other multinational companies. The leadership factors have value for organization development and leadership training.